Man the unknown - Alexis Carrel; CARREL (Alexis) (Mumbai Wilco Publishing House, 1959)
Man, The Unknown is a best-selling book by Alexis Carrel where he endeavors to outline a comprehensive account what is known and more importantly unknown of the human body and human life. Dr. Alexis Carrel, one of the truly great scientists who ever lived, tells us what man is in terms of his mental and physical make-up$1 (Band how he can become the actual rule of his universe if he learns to use wisely his amazing, God-given powers. Thus, modern society has been built at random, according to the chance of scientific discoveries and to the fancy of ideologies, without regard for the laws of our body and soul. We have been the victims of a disastrous illusion--the illusion of our ability to emancipate ourselves from natural laws. We have forgotten that nature never forgives. The book elucidates problems of the modern world, and possible routes to a better life for human beings.s
Keywords: American English Essays; American English Literature